2007
DOI: 10.1021/bk-2007-0974.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Vanadium Compounds: Pulmonary and Immune System Targets

Abstract: Inhalation is the most prevalent route of human exposure to insoluble pentavalent vanadium(V) oxides and soluble salts in urban/occupational settings. While initial pulmonary clearance of both soluble and insoluble forms of V is fairly rapid, complete clearance/degree of absorption of any V agent is ultimately a function of its solubility. Nevertheless, there are still several general toxicologic outcomes that arise from lung deposition of various V agents (as pure compounds or Vcontaminated dusts). Workers ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…2 Several studies reported an incidence increase of innate and adaptive immune cells in numerous lung diseases (such as bronchitis, pneumonia, asthma). 85,86 Grabowski et al 87 reported that exposure of a much higher concentration of rat alveolar macrophages to a vanadium compound (sodium metavanadate) resulted in a general, increased dose-dependent (from 50 μ m ) intracellular ROS generation. This resulted in further activation of NADPH oxidase, sequel to tyrosine phosphorylation of cellular proteins.…”
Section: Vanadiummentioning
confidence: 99%
“…2 Several studies reported an incidence increase of innate and adaptive immune cells in numerous lung diseases (such as bronchitis, pneumonia, asthma). 85,86 Grabowski et al 87 reported that exposure of a much higher concentration of rat alveolar macrophages to a vanadium compound (sodium metavanadate) resulted in a general, increased dose-dependent (from 50 μ m ) intracellular ROS generation. This resulted in further activation of NADPH oxidase, sequel to tyrosine phosphorylation of cellular proteins.…”
Section: Vanadiummentioning
confidence: 99%
“…Inhalation is the most prevalent route of human exposure to insoluble pentavalent V oxides and soluble salts in urban/occupational settings. Workers exposed to V-bearing dusts or fumes display an increased incidence of several lung diseases (e.g., asthma, bronchitis, pneumonia) [85]. Exposure to V can also take place through the smoking of cigarettes.…”
Section: Vanadiummentioning
confidence: 99%